Implementation of lightweight cryptographic primitives - Hammad B.T.; Jamil N.; Rusli M.E.; ZAba M.R.; Ahmed I.T. (Asian Research Publishing Network, 2023)
Lightweight cryptography is not a new branch in cryptography. It is a subject specifically addressing the implementation of security mechanism in pervasive computing that are characterized by smart but resource constrained devices. There are at least two main lightweight symmetric cryptographic primitives namely lightweight block cipher and lightweight hash algorithm. Most of the previous surveys were focusing on implementation of specific cryptographic primitives. In this paper we present a comprehensive survey of all lightweight symmetric cryptographic primitives, from hardware and software perspectives. The survey covers analysis of these algorithms and a comparison between these primitives in terms of throughput, number of cycle, comprehensive area, power, and energy. We also provide a classification of the structure of lightweight block cipher and lightweight hash function. These classifications are very useful because the primitives have different and sometimes contrary characteristics. Finally this comprehensive survey highlights some of the issues related to security aspect of small key length in lightweight cryptographic primitives. 2005 ongoing JATIT & LLS.